Application of identification method for control of bearing wear - V. Yu. Kobenko; S. O. Frolov; R. F. Ganeev (Омский научный вестник)
The work is devoted to the problem of bearings wear control of during their operation. Well-known methods for control the state of bearings to solve this problem are described. The use of the technology of identification measurement of signals to control the degree of wear of bearings is considered.